2012
DOI: 10.5430/jhm.v2n3p63
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chemotherapy-induced neutropenia on survival in patients with breast, ovarian and cervical cancer: a systematic review

Abstract: Background: Recent advances in chemotherapy administration, including targeted therapies and dose-dense scheduling have led to an increased incidence of neutropenia. Chemotherapy-induced neutropenia has been shown to be associated with improved treatment outcomes in various solid tumor types. We looked to summarize the relationship between chemotherapy-induced neutropenia and survival in patients with breast, ovarian and cervical cancer and describe future directions of research. Methodology/Principle findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
1
7
1
Order By: Relevance
“…Chia et al [ 35 ] comment that toxicity and clinical outcome may be more likely to correlate when the therapeutic agent targets the biological driver of the disease directly, for example, sunitinib-associated hypertension [ 36 ]. Although the mechanism behind the association between chemotherapy-induced neutropenia and clinical outcome is unclear, this study, in conjunction with previously published data [ 2 - 4 ], provides strong evidence that this association is real and clinically relevant.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Chia et al [ 35 ] comment that toxicity and clinical outcome may be more likely to correlate when the therapeutic agent targets the biological driver of the disease directly, for example, sunitinib-associated hypertension [ 36 ]. Although the mechanism behind the association between chemotherapy-induced neutropenia and clinical outcome is unclear, this study, in conjunction with previously published data [ 2 - 4 ], provides strong evidence that this association is real and clinically relevant.…”
Section: Discussionsupporting
confidence: 78%
“…Many studies in different tumour types have investigated the association between survival and measures of myelosuppression. Eskander et al [ 2 ] reviewed seven breast cancer studies with inter-study heterogeneity in trial design and varying toxicities, including leukocyte nadir, myelosuppression and neutropenia. The largest study [ 3 ] (n = 750), showed that patients with grade 2 or 3 neutropenia, on the National Cancer Institute Common Toxicity Criteria for Adverse Events (NCI CTCAE) scale, had a 10 % absolute survival advantage at 5 years compared to those with no neutropenia (multivariable P = 0.037).…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that local intratumoral and systemic Dox effects are not always related. Clinical observations that hematologic toxicity is the best surrogate parameter for an adequate and curative dose [45,46] could not be confirmed in our findings. In our model tissue efflux of a temporarily retained Dox was consistently resulting in subsequent tumor relapse.…”
Section: Discussioncontrasting
confidence: 79%
“…The parallels of cytotoxicity and myelosuppression indicate that the availability of Dox in a tumor microenvironment might be monitored by WBC and neutrophil counts [45,46]. However, its wide clinical implementation needs some further improvements.…”
Section: Discussionmentioning
confidence: 99%
“…Because body surface area (BSA) dosing does not account for the complex processes of cytotoxic drug elimination, an unpredictable variation in effect may occur leading to easily recognized over-dosing as well as under-dosing, the latter resulting in significantly reduced anti-cancer effect. For this reason, some investigators advocate a "toxicity adjusted dose" in which drug-specific toxicity may be used as a biomarker for accurate dosing [4]. Because GOG-182 contains the largest number of primary advanced ovarian/peritoneal carcinoma that have been prospectively treated with the current standard chemotherapy regimen of carboplatin plus paclitaxel, we chose to use this study to test the hypothesis that chemotherapy-induced neutropenia may serve as a clinical biomarker for survival in this population.…”
Section: Introductionmentioning
confidence: 99%